Interpersonal Communication in Mentoring Changes in Community Behavior in The Program Keluarga Harapan (PKH) - Khairullah; Nasution, Nadya Amalia; Syahim (Institut Pertanian Bogor, 2024)
Sukamarga Village in Suoh District, West Lampung Regency, is where the PKH program was implemented. This program aims to improve beneficiaries’ welfare through a holistic approach. However, to achieve changes in the behavior of PKH recipient communities, aspects of interpersonal communication that influence the effectiveness and success of this program are yet to be widely researched. The research problem formulated in this study is how the interpersonal communication of PKH facilitators influences changes in the behavior of PKH beneficiary families, and how the behavior of PKH beneficiary families in Sukamarga Village changes after receiving PKH. This research aims to understand the interpersonal communication of PKH facilitators regarding changes in the behavior of families who receive PKH benefits in Sukamarga Village after PKH assistance. This type of research used qualitative field research. The data sources were PKH companions and recipients. Data collection techniques included observations, interviews, and documentation. Conclusions can be drawn: First, PKH facilitators help create positive changes in beneficiary communities with empathy, guidance, and support, building trust and open communication, which are the characteristics of interpersonal communication. Second, the assistance provided was able to change the behavior of PKH recipients.